(untitled) (Nordic Journal of African Studies, 2009)
The article explores theoretical implications of sexual and violent practices among disenfranchised young men in Southern Africa. Ethnographic findings from Maputo, Mozambique indicate that massive unemployment caused by neo-liberal reforms have led to a growing number of young men basing their authority vis-à-vis women on bodily powers, understood as abilities and physique of the male body, rather than on economic powers and social status. While young men from the city’s growing middle class enact hegemonic masculinities in relationships to female partners, by means of financial powers and adherence to a ‘breadwinner’ ideology, poor young men react to a situation of unemployment and poverty by enacting masculinities that are subordinate vis-à-vis middle class peers, but which find expression through violence or sexual performance vis-à-vis female partners.